Selected Metabolites of Biofunctional Importance from Edible Fruits of Forest Shrubs - Anna Przybylska-Balcerek; Kinga Stuper-Szablewska (Molecules)
This study focused on determining the content of bioactive compounds in selected fruits of wild shrubs. The plants selected for the study were from the Rosaceae and Adoxaceae families. Particular attention should be paid to the fruits of plants commonly growing in Poland (temperate climate), such as Crataegus monogyna, Sorbus aucuparia, Viburnum opulus, and Sambucus nigra. The study aimed to deepen the knowledge of the content of selected secondary metabolites, such as phenolic acids, flavonoids, flavonoid glycosides, and their antioxidant properties, as well as natural dyes. During this study, chromatographic and spectrophotometric methods were used to determine the quantitative profile of the above-mentioned secondary metabolites of wild plant fruits. The quantitative profile of 16 phenolic acids, 9 flavonoids, 5 organic acids, 13 flavonoid glycosides, and 3 natural dyes was determined. Based on the studies, it was noted that the qualitative and quantitative profile of the bioactive compounds differs not only depending on the species but also on the location where the plant grows. A statistical analysis showed significant differences (p < 0.05) in the content of phenols and flavonoids in fruits collected from different locations. Interestingly, differences were also observed within the species, probably depending on the geographical location and composition of the soil in which the plants were grown.